From muscle quality to metabolic health: investigating the association between muscle quality index and metabolic syndrome in adults - Wen Chen; Debin Chen; Yizhou Zhuang; Liying Xu; Yaojie Wang; Youlan Chen; Yining Li; Jianhui Zhao (Diabetology & Metabolic Syndrome)
Abstract Objective Metabolic syndrome (MetS) has a high prevalence in the United States (US); however, limited research comprehensively evaluates the relationship between muscle quality index (MQI) and MetS. This study aims to investigate the association between MQI and MetS. Methods Adults aged 20–60 years from the 2011–2014 National Health and Nutrition Examination Survey were included. Handgrip strength (HGS) was measured using a dynamometer, and appendicular skeletal muscle mass (ASM) was assessed via dual-energy X-ray absorptiometry. MQI_total was calculated as the sum of HGS from both hands divided by ASM. Weighted multivariable logistic regression models and restricted cubic splines (RCS) were used to explore the association between MQI_total and MetS, and subgroup, interaction, and sensitivity analyses were conducted. Results A total of 4,503 US residents were included in the study, with 1,165 diagnosed with MetS, yielding a prevalence of 25.9% (1,165/4,503). The weighted multivariable logistic regression model indicated that after adjusting for multiple covariates, MQI was negatively associated with the risk of MetS (odds ratio [OR] = 0.49, 95%CI: 0.32–0.73). Among the different components of MetS, MQI was negatively associated with elevated waist circumference (OR = 0.19, 95%CI: 0.12–0.28), elevated high-density lipoprotein cholesterol (OR = 0.66, 95%CI: 0.51–0.85), and elevated serum triglycerides (OR = 0.66, 95%CI: 0.51–0.85). RCS revealed a negative linear relationship between MQI and MetS (P < 0.001, P non−linear = 0.98). Conclusion Low MQI is associated with an increased risk of MetS, exhibiting a linear relationship. These findings suggest that improving muscle quality may be an effective strategy for the prevention of MetS.